The impact of age and severity of comorbid illness on outcomes after isolated aortic valve replacement for aortic stenosis - Russo MJ; Iribarne A; Chen E; Karanam A; Pettit C; Barili F; Shah AP; Saunders CR (Dove Medical Press, 2015)
Mark J Russo,1,2 Alexander Iribarne,3 Emily Chen,2 Ashwin Karanam,2 Chris Pettit,2 Fabio Barili,4 Atman P Shah,5 Craig R Saunders1,2 1Barnabas Health Hospital, Newark/Livingston, NJ, USA; 2Barnabas Health Cardiovascular Clinical Research Center, Newark, NJ, USA; 3Duke University, Durham, NC, USA; 4Department of Cardiovascular Surgery, S Croce Hospital, Cuneo, Italy; 5University of Chicago, Chicago, IL, USA Objectives: This study examines outcomes in a national sample of patients undergoing isolated aortic valve replacement (AVR) for aortic stenosis, with particular focus on advanced-age patients and those with extreme severity of comorbid illness (SOI). Methods: Data were obtained from the Nationwide Inpatient Sample and included all patients undergoing AVRs performed from January 1, 2006 to December 31, 2008. Patients with major concomitant cardiac procedures, as well as those aged <20 years, and those with infective endocarditis or aortic insufficiency without aortic stenosis, were excluded from analysis. The analysis included 13,497 patients. Patients were stratified by age and further stratified by All Patient Refined Diagnosis Related Group SOI into mild/moderate, major, and extreme subgroups. Results: Overall in-hospital mortality was 2.96% (n=399); in-hospital mortality for the ≥80-year-old group (n=139, 4.78%) was significantly higher than the 20- to 49-year-old (n=9, 0.84%, P<0.001) or 50- to 79-year-old (n=251, 2.64%, P<0.001) groups. In-hospital mortality was significantly higher in the extreme SOI group (n=296, 15.33%) than in the minor/moderate (n=22, 0.35%, P<0.001) and major SOI groups (n=81, 1.51%, P<0.001). Median in-hospital costs in the mild/moderate, major, and extreme SOI strata were $29,202.08, $36,035.13, and $57,572.92, respectively. Conclusion: In the minor, moderate, and major SOI groups, in-hospital mortality and costs are low regardless of age; these groups represent >85% of patients undergoing isolated AVR for aortic stenosis. Conversely, in patients classified as having extreme SOI, surgical therapy is associated with exceedingly high inpatient mortality, low home discharge rates, and high resource utilization, particularly in the advanced age group. Keywords: cardiac surgery, outcomes, risk stratification